3D printing of curved continuous carbon fibre reinforced polymer composites - Zhang, Haoqi (The University of Edinburgh, 2021)
Fused filament fabrication (FFF) 3D printing technology offers the opportunity to change the orientation of continuous fibres during the manufacturing process. This thesis investigates the fibre placement method, the printing quality of continuous filaments and the post-processing technique of the printed preforms, in order to manufacture the lightweight 3D-printed composites with curved continuous fibre reinforcements. First, a new concept to place continuous curved fibres along principal stress trajectories is presented. Three cases under different loading conditions are studied numerically and compared with traditional composites reinforced with unidirectional fibres. The modelling results show that the stress concentration in both fibre and matrix are reduced significantly by the curved fibre placement and the stiffness of CFRP composites has been improved. Secondly, a tailored fibre placement is achieved in the 3D printing experiment by altering the fibre orientation to leave a hole. The modelling and failure analysis are then conducted for 3D-printed woven composite plates with a hole under tensile and shear loading. Good agreement between numerical and experimental results is obtained, which exhibits a similar trend of strength improvement using the new placement technique. After that, the mechanism of the void formation and manufacturing-induced defects during the printing process is investigated. Single printed stripe at various turning angles and curvatures are characterised using X-ray computed micro-tomography (µCT) scanning and optical microscopy. A finite element (FE) model of the printing process is also established to support the experimental measurement. It has been found that the void content and fibre misalignment result from the weak fibre/matrix interface and the uneven pressure executed by the nozzle. The increase of turning angle leads to more aggravated printing defects, including path inaccuracy, fibre twisting, folding and even fibre breakage. Further, a hybrid technique is developed to manufacture composites with low porosity and customised curved fibre paths. Composite preforms are manufactured by FFF 3D printing and powder thermoset epoxy is added to the preforms to fill up the gaps, remove air voids and enhance the interfacial bonding through traditional vacuum bagging and oven curing process. In the standard UD 0° samples, the tensile stiffness and strength are increased by 29.3% and 22.1%, respectively. The hybrid manufacturing technique is also adopted to investigate the performance of the single-notched specimen under uniaxial tension. It is shown that the placement of continuous fibres along the principal stress trajectories significantly increased the failure strength as well as the fracture toughness of the composites. Besides, the effect of fibre placement on the mechanical performance of open-hole composites under uniaxial tension is comprehensively studied. The concept of placing continuous fibres along the higher in-plane principal stress trajectories is found to improve the strength of the composites and postpone the crack initiation. Additional fibres, along the lower in-plane principal stress trajectories and around the hole, are found to alter the failure mode and mechanical performance of the samples. Together with the digital image correlation measurement, a FE model is also built based on the actual printing paths to understand the stress distributions due to different fibre placement methods. Finally, a sequentially coupled optimisation for structural topology and fibre orientation is presented. Topology optimisation is first carried out to obtain the geometry of the structure and then the continuous carbon fibres are placed along the identified principal stress trajectories. Case study of Messerschmitt-Bolkow-Blohm (MBB) beam under three-point bending is performed. Compared with the state-of-the-art printing system, the strength and stiffness of the optimised sample are increased by 305% and 256%, respectively. With only 20% fibre usage, the optimised sample can achieve the same stiffness-to-weight ratio as the traditionally-manufactured composites.
Keywords: 3D printing; fused filament fabrication (FFF); curved continuous carbon fibre; topology optimisation; principal stress trajectories